2021
DOI: 10.1177/00472395211067731
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact on Teacher Preparedness as a Result of Using Mursion as a Risk-free Microteaching Experience for Pre-service Teachers

Abstract: Risk-free micro-teaching affords an opportunity for pre-service teachers (PTs) to practice teaching and student engagement techniques outside of a traditional classroom setting. More time to practice teaching is often an expressed desire of PTs. Orchestrating time to practice teaching techniques learned in pedagogy courses is a difficult undertaking for teacher educators, especially while trying to ensure low-risk or risk-free experiences. As explained through this study, the implementation of a Mursion simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…However, our results show that the user experience would have been better with more interactions. Consistent with other studies (Ferguson and Sutphin 2022;Huang and Lee 2022;Lugrin et al 2016;Mouw et al 2020), limitations in interacting with virtual learners was a constraint highlighted by most participants. In line with Engel and Coll (2022), this constraint prevents the learner from connecting with the information provided by the technology in order to make strategic decisions in relation to the goals of the learning task, and this may affect motivation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, our results show that the user experience would have been better with more interactions. Consistent with other studies (Ferguson and Sutphin 2022;Huang and Lee 2022;Lugrin et al 2016;Mouw et al 2020), limitations in interacting with virtual learners was a constraint highlighted by most participants. In line with Engel and Coll (2022), this constraint prevents the learner from connecting with the information provided by the technology in order to make strategic decisions in relation to the goals of the learning task, and this may affect motivation.…”
Section: Discussionsupporting
confidence: 88%
“…A significant number of research has delved into the utilization of various VR simulations for pre-service teacher training, as evidenced by studies such as those conducted by Lugrin et al (2016), Mouw et al (2020), and Ferguson and Sutphin (2022). Their findings underscore the imperative need to enhance realism and presence in VR simulations.…”
Section: Virtual Reality Learning Environment For Teacher Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study found that preparation among preservice teachers contributed to the effective teaching in teaching approach, teaching method, and teaching strategy. Hence, focusing on preparation is important as highlighted in the previous studies (Ferguson & Sutphin, 2022;Ima Isnaini, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…With better preparation, preservice teachers perceive positively towards their teaching in terms of teaching approach, teaching methods, and teaching strategies. Readiness from the basis of preparation was highly emphasized in previous studies (Ferguson & Sutphin, 2022). Effective preparation provides exceptional results in teaching, especially enhancing preservice skills such as communication, critical thinking and problem solving (Popovich & Katz, 2009).…”
Section: Discussionmentioning
confidence: 99%